PLA2R-positive (primary) membranous nephropathy in a child with IPEX syndrome - Chuva, Teresa; Pfister, Frederick; Beringer, Ortraud; Felgentreff, Kerstin; Buettner-Herold, Maike; Amann, Kerstin Ute (Pediatric Nephrology, 2017)
Immunodysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) syndrome is a rare primary immunodeficiency syndrome characterized by the development of multiple autoimmune disorders in affected individuals. Different forms of renal injury have been reported in IPEX syndrome, and membranous nephropathy (MN) is among the most common glomerulopathies found. However, the exact pathogenesis of MN in this setting has not been elucidated, and it is not clear whether it is part of the clinical spectrum of the disease or secondary to medications, infections or other concomitant insults.We describe a child diagnosed with IPEX syndrome shortly after birth who presented with nephrotic syndrome at the age of 11 weeks. Renal biopsy revealed a MN with enhanced immunohistochemical staining for phospholipase A2 receptor (PLA2R).This is the first report of a PLA2R-positive MN in a patient with IPEX syndrome. We suggest that, in this context, MN results from an autoimmune process against podocytic antigens, namely PLA2R.
EVALuna2:25544